2022
DOI: 10.1002/btm2.10283
|View full text |Cite
|
Sign up to set email alerts
|

Use of FLOSEAL® as a scaffold and its impact on induced neural stem cell phenotype, persistence, and efficacy

Abstract: Induced neural stem cells (iNSCs) have emerged as a promising therapeutic platform for glioblastoma (GBM). iNSCs have the innate ability to home to tumor foci, making them ideal carriers for antitumor payloads. However, the in vivo persistence of iNSCs limits their therapeutic potential. We hypothesized that by encapsulating iNSCs in the FDA‐approved, hemostatic matrix FLOSEAL®, we could increase their persistence and, as a result, therapeutic durability. Encapsulated iNSCs persisted for 95 days, whereas iNSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The most significant challenge with neural stem cell therapy for treatment of post-surgical GBM is the fast clearance observed from the site of implantation. Several commercially available and synthetic-based polymer systems have been investigated as a delivery approach to overcome this clinical limitation [ 13 , 14 , 15 , 16 , 17 , 18 ]. However, there are several factors to consider when designing a polymer-based scaffold material to encapsulate and deliver neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most significant challenge with neural stem cell therapy for treatment of post-surgical GBM is the fast clearance observed from the site of implantation. Several commercially available and synthetic-based polymer systems have been investigated as a delivery approach to overcome this clinical limitation [ 13 , 14 , 15 , 16 , 17 , 18 ]. However, there are several factors to consider when designing a polymer-based scaffold material to encapsulate and deliver neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies that have explored the use of biomaterials for the delivery of NSCs, the present work has focused on elucidating the impact of (1) NSCs on biomaterial properties and (2) biomaterials on NSC functionality [ 13 , 14 , 15 , 16 , 17 , 18 ]. Although previous studies showed that other scaffold materials possess the ability to enhance in vivo NSC persistence, in the present report we highlight key features and/or properties that can influence overall efficacy of NSC-laden CS and CS-CNC hydrogels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FLOSEAL-encapsulated, TRAIL-secreting hiNSCs persisted in the brain for 95 days in a murine recurrent GBM model, and the mice survived 30–60 days longer than the control mice that were treated with nonencapsulated TRAIL-secreting hiNSCs. 58 Hence, patient-derived tumor-homing stem cells that deliver TRAIL to tumor sites hold potential as drug delivery vehicles.…”
Section: Gene and Cell Therapymentioning
confidence: 99%
“… 91 For example, patients could receive maximal surgical resection and TRAIL-secreting personalized stem cells encapsulated with biodegradable hemostatic agents such as FLOSEAL to prevent tumor recurrence. 58 , 92 In addition, TRAIL sensitizers could minimize the effects of TRAIL resistance. For patients who are ineligible for surgery, chemotherapy, and radiation could be accompanied by administration of either TRAIL proteins encapsulated NPs or TRAIL genes encapsulating NPs to target both intrinsic and extrinsic apoptotic pathways.…”
Section: Conclusion and Perspectivementioning
confidence: 99%